Management of Blunt Trauma to the Spleen in Children; A review Part II. Seyed Abbas Banani. (We are sorry to inform you that due to duplicate publication of this article. we are required to take it down.) - Chief Editor of IRJPS (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
.